Communities as a Subject of Social Fabric Construction in the Colombian Catatumbo Region - Alba‐Niño, Magali (Bulletin of Latin American research, 2024)
The community actions developed by the inhabitants of marginalised communities by Idler and McGill have contributed to the construction of a social base for peace, favouring cohesion and the reproduction of social life in the resistance to years of armed conflict, state abandonment and other social phenomena. The Catatumbo region in Colombia has been the focus of several analyses regarding the visibility of public and private organisations that have come to the territory to provide perishable assistance, which do not constitute a holistic social project involving all aspects of the conflict and its impact on the community. This prevents the recognition of the figure of collective social subject that contributes to the construction of a social basis for peace. In this sense, this article is intended to address the contribution of the communities as collective subject to the construction of the social fabric, recognising the different initiatives that have been developed by the subjects who inhabit the region from their historical‐political role.